Future Challenges for the Port and Shipping Sector. - Meersman, Hilde (Grammenos library., 2014)
Future Challenges for the Port and Shipping Sector discusses the issues that most influence the future of the maritime and port industries. Important topics covered in this book include: Maritime trade, future trade flows, evolutions in international trade, shipping capacity and demand Developments in ship construction and their economic consequences Future developments in ports: technology and economics The future role of port authorities The future development in ports Financial developments This book looks at shipping from an holistic point of view and will be especially compe.